The experiences of gay and bisexual men diagnosed with prostate cancer: results from an online focus group. (3rd June 2013) - Thomas, C.; Wootten, A.; Robinson, P.
Abstract : Research concerning gay and bisexual men diagnosed with prostate cancer is sparse. An online focus group was conducted over a 4‐week period with participants responding to a range of discussion questions concerning their experiences following a prostate cancer diagnosis. Emerging themes were identified and consensus reached. A summary of each of the themes was produced which the coders agreed conveyed the essence of the online discussion. All men who took part in the online focus group reported that prostate cancer significantly impacted their lives. Unexpectedly, some participants actually gained a positive perspective and adopted a sense of empowerment. Participants spoke about emotional responses to a diagnosis of prostate cancer, accessing help and support, the impact of incontinence, the impact of sexual changes on identity, a re‐evaluation of life, changed sexual relationships, the need to find the most suitable healthcare professionals and identification of current needs to improve quality of care. These areas of disquiet suggest that the psychological impact of this disease may be quite significant over an extended time‐frame. Further research needs to be undertaken to assess the degree of distress accompanying the treatment of gay and bisexual men with prostate cancer.